Microstructure and thermal properties of unalloyed tungsten deposited by Wire + Arc Additive Manufacture - Marinelli, Gianrocco; Martina, Filomeno; Lewtas, Heather; Hancock, David; Mehraban, Shahin; Lavery, Nicholas; Ganguly, Supriyo; Williams, Stewart W. (Elsevier, 2019)
Tungsten is considered as one of the most promising materials for nuclear fusion reactor chamber applications. Wire + Arc Additive Manufacture has already demonstrated the ability to deposit defect-free large-scale tungsten structures, with considerable deposition rates. In this study, the microstructure of the as-deposited and heat-treated material has been characterized; it featured mainly large elongated grains for both conditions. The heat treatment at 1273 K for 6 h had a negligible effect on microstructure and on thermal diffusivity. Furthermore, the linear coefficient of thermal expansion was in the range of 4.5 × 10−6 μm m−1 K−1 to 6.8 × 10−6 μm m−1 K−1; the density of the deposit was as high as 99.4% of the theoretical tungsten density; the thermal diffusivity and the thermal conductivity were measured and calculated, respectively, and seen to decrease considerably in the temperature range between 300 K and 1300 K, for both testing conditions. These results showed that Wire + Arc Additive Manufacture can be considered as a suitable technology for the production of tungsten components for the nuclear sector.
Keywords: WAAM; Tungsten; Microstructure; Thermal properties; Nuclear fusion; Thermal conductivity